Impact of Side Friction Parameters to Road Performance, A Study of Road Side Activities to Jend. A Yani Road, Purbalingga - Hardini, Probo; Indriyati, Eva Wahyu; Ahmad Termida, Nursitihazlin; Janudardono, Wibowo (2025)
Traffic flow on city roads is greatly affected by side friction elements, like parking on the street, pedestrian crossings, and non-motorized vehicles (NMVs), mainly in areas with mixed traffic. This study looks at these effects on Jenderal A. Yani Road in Purbalingga, Indonesia, which is an important industrial route that links key manufacturing sites and sees a lot of vehicle and foot traffic. The goals of the research are to (1) find the side friction factor that most impact vehicle space mean speed (SMS), (2) use multivariate regression to understand the link between side friction and SMS, and (3) determine which traditional traffic flow model—Underwood, Greenshield, or Greenberg—best fits the observed flow patterns in mixed-traffic situations. Early results indicate that stopped vehicles are the biggest friction element that lowers SMS, while pedestrian crossings and NMVs also lead to delays during busy times. The Underwood model, which shows how speed decreases exponentially with increasing density, is the most accurate for depicting traffic dynamics on Jenderal A. Yani Road, with a critical density of 9.75 vehicles per km suggesting the start of congestion. These findings are useful for creating plans that improve traffic flow in urban-industrial areas. By addressing side friction and using the right traffic models, the research aids in developing data-informed approaches to enhancing the Level of Service (LOS) on roads with high friction, especially in developing nations facing similar traffic challenges. This work helps in managing urban traffic by laying the groundwork for planning that accommodates mixed traffic and lessens congestion.